Legal protection of legal document holders of land rights - Kuswanto, Heru; Suhartono, Slamet; Prasetyawati, Endang; Setyadji, Sri (Technium Social Sciences Journal, 2021)
This type of research is normative legal research. Land has a very important meaning for humans, because it’s the place where humans depend on their life and death. Land is a need that continues to increase from time to time for various purposes. The importance of land is not only for humans or society, but also for private and public legal entities. The increasing need for land causes the availability of land to decrease, which causes the economic value of land to continue to increase. The limited availability of land for various purposes has resulted in frequent disputes over land rights, the resolution of which often involves the court, with a decision in favor of one of the parties. The legal document of the right to rights has not been able to guarantee legal protection for the holder. This is due to many factors, including the land registration system which adheres to a negative system which tends to be positive, which allows the emergence of claims from third parties, which can prove otherwise